2022
DOI: 10.1038/s43247-022-00426-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow stimulates chemoautotrophy in hydrothermally influenced coastal sediments

Abstract: Hydrothermalism in coastal sediments strongly impacts biogeochemical processes and supports chemoautotrophy. Yet, the effect of fluid flow on microbial community composition and rates of chemoautotrophic production is unknown because rate measurements under natural conditions are difficult, impeding an assessment of the importance of these systems. Here, in situ incubations controlling fluid flow along a transect of three geochemically distinct locations at a shallow-water hydrothermal system off Milos (Greece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…The genus Thiomiscrospira, and the strain Thiomicrospira sp. Milos-T1 isolated at Milos, has been suggested to be a major actor of sulfur oxidation in Paleochori Bay (Brinkhoff et al, 1999), but these results were not supported in a recent study (Sievert et al, 2022(Sievert et al, ), 10.3389/fmicb.2022 Frontiers in Microbiology 15 frontiersin.org and in our dataset the family Thiomicrospiraceae is mainly present only in the yellow patch composition. Similarly, the family of the sulfur oxidizing bacteria Halothiobacillus kellyi isolated at Milos (Sievert et al, 2000b) represents at best 0.9% of any sample.…”
Section: Sulfur Cyclingcontrasting
confidence: 99%
See 4 more Smart Citations
“…The genus Thiomiscrospira, and the strain Thiomicrospira sp. Milos-T1 isolated at Milos, has been suggested to be a major actor of sulfur oxidation in Paleochori Bay (Brinkhoff et al, 1999), but these results were not supported in a recent study (Sievert et al, 2022(Sievert et al, ), 10.3389/fmicb.2022 Frontiers in Microbiology 15 frontiersin.org and in our dataset the family Thiomicrospiraceae is mainly present only in the yellow patch composition. Similarly, the family of the sulfur oxidizing bacteria Halothiobacillus kellyi isolated at Milos (Sievert et al, 2000b) represents at best 0.9% of any sample.…”
Section: Sulfur Cyclingcontrasting
confidence: 99%
“…In areas of hydrothermal activity, the advective influx of reduced sulfur species can also fuel the growth of sulfur oxidizing organisms (Sievert et al, 2008(Sievert et al, , 2022. At Milos, the fluids contain abundant H 2 S (Fitzsimons et al, 1997), and the sulfidic zone has been shown to reach or nearly reach the seafloor, except directly at the vent where seawater microcirculation allows for oxygen to penetrate a few centimeters (Wenzhöfer et al, 2000;Yücel et al, 2013).…”
Section: Sulfur Cyclingmentioning
confidence: 99%
See 3 more Smart Citations